SIGNIFICANT FACTORS INFLUENCING HYPERBILIRUBINEMIA AT SANTO YUSUF MOTHER AND CHILD HOSPITAL, NORTH JAKARTA USING BINARY LOGISTIC REGRESSION - Pratiwi, Elsa Anna; Nurhayati, Nunung; Sihwaningrum, Idha (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2024)
Hyperbilirubinemia is a problem that often occurs in newborns. The cause of hyperbilirubinemia is multifactorial including maternal, perinatal or environmental factors that can be risk factors in newborns. Hyperbilirubinemia that occurs in infants is usually due to high bilirubin levels. High bilirubin can be a poison that causes brain damage so hyperbilirubinemia must be treated appropriately so as not to cause chronic complications. This study aims to identify significant factors affecting hyperbilirubinemia in infants at Santo Joseph Mother and Child Hospital, North Jakarta using binary logistic regression. This research was conducted at Santo Joseph Mother and Child Hospital for the first time. Factors that are thought to influence are gestational age, birth weight, childbirth, breastfeeding, and infection status. The results showed that the significant factors affecting hyperbilirubinemia in infants were the process of childbirth, milk feeding and infection status. Based on the odds ratio value for each variable, it can be concluded that babies with abnormal birth processes have a risk of hyperbilirubinemia of 2.9628 times greater than babies with normal births. Meanwhile, formula-fed infants have a risk of hyperbilirubinemia of 4.2854 times less than breastfed babies. Furthermore, infants affected by infection have a risk of developing hyperbilirubinemia of 5.5752 times greater than infants who do not get infection.